Komunikasi Keluarga terhadap Keterbukaan Diri Mahasiwa Perantau - Rina Astriani; Rani Puspita (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to explore family communication in the self- disclosure of students living away from home in Yogyakarta. The theory used in this study is the Self-Disclosure theory. The research method used is a qualitative. Data collection techniques used in this study were interviews, observation, and various sources of literature. The results of the study show that open and empathetic communication between parents and children are crucial for building trust and emotional support. The openness in sharing experiences and feelings helps students feel more connected to their families, which, in turn, enhances their ability to adapt to new environments. This research underscores the importance of creating a supportive communication environment for students living away from home to thrive optimally.